The Requirements Of Strategic Planning For Crisis And Disaster Management (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of the research is to determine the requirements of strategic planning in each stage of crisis management (the stage of awareness of the crisis, the stage of preparing to face the crisis, the stage of confronting the crisis, and the stage of crisis evaluation), from the point of view of the active volunteers in the departments of the Syrian Arab Red Crescent.The research was based on the descriptive approach, and the research community included all active volunteers with experience in crisis and disaster management in the departments of the Syrian Arab Red Crescent Organization (disaster management department, health care department, water and sanitation department, community need response department, human resource development and capacity building department The number of volunteers is approximately (130) active volunteers, where the researcher distributed the questionnaire to the search tool, from which (111) questionnaires were returned, with a response rate of (85.38%).The research found a group that the most important requirements of strategic planning for crisis and disaster management require awareness and the formation of a system to detect early warning of the crisis, planning and pre-preparation of potential crises, determining the material and human capabilities to implement the plan to manage the crisis, the presence of an emergency team to deal with the crisis, and the provision of rational leadership that has experience Coordinating the work of volunteers and training them on crisis response work, assessing previous crises and uncovering any deficiencies or defects in the process of facing them to prevent their recurrence, in addition to following up on the implementation of remedial measures and dealing with emergency events that may occur after crises.